Geographical and Ethnic Differences Influence Culturable Commensal Yeast Diversity on Healthy Skin - Leong, Cheryl; Schmid, Bettina; Toi, Min Jet; Wang, Joyce; Irudayaswamy, Antony Sagayaraj; Goh, Joleen Peh Zhen; Bosshard, Philipp P.; Glatz, Martin; Dawson, Thomas L. (Frontiers in Microbiology, 2019)
Commensal fungi such as Malassezia, Candida and Rhodotorula are common on healthy skin but have also been associated with opportunistic invasive and superficial infections. Studies on skin microbial community characterization have been extensively performed worldwide, with a focus on the 16S bacterial community. These studies have focused on geographically distinct or targeted cohorts with variable reported species distributions of commensal yeast species. To determine the effects of extrinsic environmental factors such as geography, climate, and ethnicity on detected healthy skin commensal yeast diversity, we compared cohorts from Singapore and Zurich, Switzerland, representative of two geographically and climatically distinct regions comprising multi-ethnic (Chinese, Malay, Indian, Caucasian) and predominantly white Caucasian cohorts, respectively using identical skin sampling and culture methods. We chose to use a culture-based approach as cultures isolated from patients are still required for studies of pathogenicity and antifungal susceptibility. Detection of yeast species by culture-dependent and independent sequencing based methods suggest healthy skin diversity reflects a species distribution representative of the geography, climate and ethnic background of their local populations. Culture success and species diversity was also found to be dependent on climate, with warm tropical climates favouring high positive culture rates and greater species diversity. Multilocus sequence typing data suggests some strains are geographically distinct and may be used to segregate potential disease causing commensals. For accurate collection and characterization of skin microbial communities, it remains recommended to employ a combination of culture-dependent and sequence-based culture-independent methods. Characterization of healthy mycobiomes in geographically distinct local populations will be useful in defining the role of commensal fungi in health and disease.